Terapi Okupasi Aktivitas Menggambar terhadap Perubahan Halusinasi pada Pasien Skizofrenia - I Wayan Candra; I Ketut Sudiantara (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2014)
The aims of this research is to know the influence of drawing activity occupation therapy with changed hallucinations sign in schizophrenia patiens. Kind of the research is quasy experiment, one group pretest-posttest design.The sampling teqnique with non probability sampling quota sampling. The sample 30 respondents. After observing research get the most hallucination symptoms in schizophrenia patients before having drawing activity occupation therapy is in medium category that is 15 patients (50%), after having drawing activity occupation therapy the most is in low category that is 21 patiens (70%). The result of wilcoxon sign rank test get p = 0,000 p 0,010 that′s mean there is significant influence in drawing activity occupation therapy with changed hallucinations sign in schizophrenia patients.